Building a Line of Defense Against Climate Change : From Reactive Coping to Adaptive Capacity in China's Irrigated Agricultural Development - Conrad, Bjorn; Li, Qun (World Bank, Washington, DC, 2012)
Climate change threatens to undermine decades of development achievements in China's Huang-Huai-Hai River Basin. Farmers in the 3H Basin have long been plagued by water scarcity and frequent droughts and floods. Development efforts have succeeded in relieving some of these pressures, but the effects of climate change put these achievements in jeopardy. The mainstreaming climate change adaptation in irrigated agriculture project, funded under the Special Climate Change Fund (SCCF) and integrated into the World Bank's Third Irrigated Agriculture Intensification Project, has been building a line of defense against the looming consequences of climate change on agricultural communities in China. The project was recognized as good adaptation practice in the 2011 world resources report as well as the SCCF evaluation of the independent GEF (Global Environment Facility) Evaluation Office. This smart lesson describes how the project created long-term adaptive capacity for affected communities to support sustainable irrigated agriculture in rural China.